Antihyperglycemic Activity of Petroleum Ether Leaf Extract of Ficus krishnae L. on Alloxan-induced Diabetic Rats - Sidhu, M. C. (Medknow Publications & Media Pvt Ltd, 2014)
The petroleum ether leaf extract of Ficus krishnae has been evaluated for the management of diabetes in alloxan induced diabetic rats. Phytochemical screening of the leaf extract for various chemical compounds has also been carried out. Leaf extract was administered continuously for 21 days orally at a dose of 200 mg/kg. Along with this, the blood glucose level was monitored at regular intervals to understand the activity of the extract. The leaf extract has decreased the blood glucose level of diabetic rats which was comparable to an antidiabetic standard drug, glibenclamide, given at a dose of 2.5 mg/kg. It has been observed that the leaves of Ficus krishnae possess antidiabetic activity and it reduces the blood glucose level significantly. The phytochemical screening of leaf has revealed the presence of carbohydrates, flavonoids, tannins, glycosides, terpenoids, steroids, alkaloids, gums and mucilage, phlobatannins, reducing sugars and phenolic compounds. The Fourier Transform Infrared analysis of glibenclamide and leaf powder has displayed some common absorption spectra. This shows that leaf powder has a molecule which is close to glibenclamide. Wavelength Dispersive X-Ray Fluorescence spectroscopy have shown the presence of cellulose, Ca, Si, K, Cl, Mg, P, S, Al, Fe, Na, Sr, Pd, Zn, Mn, Cr, Mo, Br, Ni, Rb and Zr. It is assumed that these elements alongwith other chemical compounds of the plant species may play a role in the management of diabetes. The Raman Specta of both glibenclamide and leaf powder has also shown some similarities. The results obtained during the present investigation have revealed the antidiabetic activity of Ficus krishnae leaves. The phytochemical screening has indicated the various chemical constituents likely to be responsible for this activity. The Fourier Transform Infrared, Wavelength Dispersive X-Ray Fluorescence and Raman Specta of the leaf powder suggested that there is some glibenclamide like molecule or its derivatives which is imparting antidiabetic activity.